Annual reports on NMR spectroscopy - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy ;, 1991)
This book is part of a series on spectroscopy, and covers NMR studies of isolated spin-pairs in the solid state, the oxidation state dependence of transition metal shieldings, the Cinderella nuclei, nuclear spin relaxation in organic systems, solutions of macromolecules and aggregates and the NMR of coals and coal products. Related titlesare volumes 20, 21 and 22 in the series.